Elevated air movement enhances stomatal sensitivity to abscisic acid in leaves developed at high relative air humidity - Carvalho, Dália R. A.; Torre, Sissel; Kraniotis, Dimitrios; Almeida, Domingos P. F.; Heuvelink, Ep; Carvalho, Susana M. P. (Frontiers in Plant Science, 2015)
High relative air humidity (RH ≥ 85%) during growth leads to stomata malfunctioning, resulting in water stress when plants are transferred to conditions of high evaporative demand. In this study, we hypothesized that an elevated air movement (MOV) 24 h per day, during the whole period of leaf development would increase abscisic acid concentration ([ABA]) enhancing stomatal functioning. Pot rose ‘Toril’ was grown at moderate (61%) or high (92%) RH combined with a negligible MOV or with a continuous MOV of 0.92 m s-1. High MOV reduced stomatal pore length and aperture in plants developed at high RH. Moreover, stomatal function improved when high MOV-treated plants were subjected to leaflet desiccation and ABA feeding. Endogenous concentration of ABA and its metabolites in the leaves was reduced by 35% in high RH, but contrary to our hypothesis this concentration was not significantly affected by high MOV. Interestingly, in detached leaflets grown at high RH, high MOV increased stomatal sensitivity to ABA since the amount of exogenous ABA required to decrease the transpiration rate was significantly reduced. This is the first study to show that high MOV increases stomatal functionality in leaves developed at high RH by reducing the stomatal pore length and aperture and enhancing stomatal sensitivity to ABA rather than increasing leaf [ABA].